The Threat of Forming a Post-Truth Scenario Through Political Propaganda by Social Media Users in the 2024 General Election - Kurniawan, Adib Rifqy (Security Intelligence Terrorism Journal (SITJ), 2025)
At the beginning of 2023, We Are Social recorded that internet users in Indonesia reached 212.9 million people, or the equivalent of 77 percent of the total population. This figure has more than doubled compared to the initial year that regulations on the use of social media as a means of campaigning were implemented, namely in 2014, which was 88.1 million people. Currently active social media users in Indonesia have reached 167 million users. The more social media users there are in Indonesia, the faster the potential for information dissemination, including the spread of hoaxes and content with hate speech nuances, which is also increasingly widespread. This condition has triggered an increase in the concentration of post-truth in Indonesia ahead of the 2024 General Election. This research will identify patterns of post-truth formation in Indonesia, as well as analyze the threat of the existence of post-truth in the midst of holding the General Election. This qualitative research will use netnographic methods by focusing on Hoax content and nuances of Hate Speech on Social Media, especially Twitter. Apart from that, interviews will also be conducted with experts, academics, and practitioners.